Photo-Triggered Release of Caged Camptothecin Prodrugs from Dually Responsive Shell Cross-Linked Micelles - Hu, Xianglong; Tian, Jie; Liu, Tao; Zhang, Guoying; Liu, Shiyong (Macromolecules, 2013)
We report on the fabrication of dynamic covalent shell cross-linked (SCL) micelles with hydrophobic cores conjugated with photocaged chemotherapeutic drugs and coronas functionalized with ligands for tumor cell targeting. Two types of amphiphilic diblock copolymers, P(CL-g-CPT)-b-P(OEGMA-co-MAEBA)-CPT and PCL-b-P(OEGMA-co-MAEBA-co-FA), were synthesized via the combination of ring-opening copolymerization (ROP) of ε-caprolactone (CL) and 2-bromo-ε-caprolactone (CL-Br), atom transfer radical polymerization (ATRP) of oligo(ethylene glycol) monomethyl ether methacrylate (OEGMA) and p-(methacryloxyethoxy) benzaldehyde (MAEBA) comonomers, and “click” post-functionalization with photocaged camptothecin (CPT) prodrug and alkynyl-functionalized folic acid (FA) moieties, respectively. Mixed micelles coassembled from PCL-b-P(OEGMA-co-MAEBA-co-FA) and P(CL-g-CPT)-b-P(OEGMA-co-MAEBA)-CPT possess hydrophobic cores conjugated with photocaged CPT prodrugs and hydrophilic outer coronas covalently attached with aldehyde groups and FA moieties for subsequent shell cross-linking and cancer cell targeting. Shell cross-linking was performed at pH 6.2 upon addition of difunctional cross-linker, dithiol bis(propanoic dihydrazide) (DTP), under the catalysis of aniline. The obtained FA-decorated SCL micelles contain acylhydrazone and disulfide linkages in the outer coronas, which can be de-cross-linked under two biologically relevant conditions, mildly acidic or reductive microenvironments, that is, endosomal/lysosomal pH or high GSH level in the cytosol. The cleavage of caged CPT drug within the cores of SCL micelles can be effectively actuated under photo irradiation, whereas its diffusion out of micellar nanocarriers can be further modulated by pH and thiol levels due to the dually responsive nature of DTP cross-linker. Compared with the control, FA-decorated SCL micelles can more efficiently enter folate-receptor expressing cancer cells than folate-receptor deficient ones. Cell viability assays revealed that SCL micelles displayed at least ∼9.7-fold enhanced cytotoxicity upon light irradiation. The reported targeting ligand decorated and prodrug-conjugated dynamic covalent SCL micelles exert intricate control concerning micellar stability, cancer cell targeting, photo-triggered parent drug release with photoactivated cytotoxicity, and tunable drug release profiles. All of these augur well for their potential application as a novel integrated platform for targeted drug delivery in cancer chemotherapy.